2005
DOI: 10.1002/clc.4960281005
|View full text |Cite
|
Sign up to set email alerts
|

Serum troponin I level after external electrical direct current synchronized cardioversion in patients with normal or reduced ejection fraction: No evidence of myocytes injury

Abstract: SummaryBackground: External electrical cardioversion (EEC) has been suggested as a cause of myocardial damage, but results from several previously published studies are conflicting.Hypothesis: The purpose of the study was to evaluate myocardial electrical injury caused by EEC.Methods: After elective EEC for atrial fibrillation (AF), cardiac troponin I (cTnI) was measured in 193 consecutive patients attending the Cardiology Department of the San Maurizio Hospital of Bolzano for elective EEC of AF over a period … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Between 1996 and 2006, 13 studies (n = 690) looked at the effect of monophasic external cardioversion on cTn level (Table I). 64–75,78 Four studies used cTnI, seven used cTnT, and two used both (cTnI, cTnT). The majority were cardioversion of A.Fib/Flut.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Between 1996 and 2006, 13 studies (n = 690) looked at the effect of monophasic external cardioversion on cTn level (Table I). 64–75,78 Four studies used cTnI, seven used cTnT, and two used both (cTnI, cTnT). The majority were cardioversion of A.Fib/Flut.…”
Section: Resultsmentioning
confidence: 99%
“…Monophasic external cardioversion caused no or only minimally insignificant elevation in cTn level, 64–75 even for induced VT/VF 78 . Overall, only 1.6% of patients who underwent monophasic external cardioversion had increase in cTn level, and it was only in the range of minimal myocardial energy (>0.1 ng/mL and <1.5 ng/mL) with a range of 0.1–0.9 ng/mL for cTnI 73–75 .…”
Section: Discussionmentioning
confidence: 95%
“…Tissue injury has been intensively studied; however, only with regard to the cardiac myocytes. Several studies on cardiac troponin levels indicated no or only minimal, clinically insignificant cardiac damage (2,7). A small single study reported a transient creatine kinase increase, pointing to skeletal muscle involvement, while another study confirmed a generalised inflammatory response, which could possibly exacerbate the thrombotic risk of EC (4,6).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that direct current flow through the patient's body can cause minimal cell injury, which has been intensively studied in the heart muscle. Most reports indicated no cardiac damage or no clinically significant damage as assessed by means of troponin concentrations (2,7). Only a single report exists regarding the possible injury of other components of the chest such as thoracic muscles (6).…”
Section: Introductionmentioning
confidence: 99%
“…Cardioversion can lead to mild cTnI rise as measured with a high-sensitivity assay [2]. There was no evidence of myocytes injury, no increase of troponin I after external electrical direct current synchronized cardioversion in patients with normal or reduced ejection fraction [3]. It was rare for electrical injury case with serious myocardial damage and death.…”
Section: Introductionmentioning
confidence: 99%